2014
DOI: 10.1038/sc.2013.166
|View full text |Cite
|
Sign up to set email alerts
|

Oral erlotinib, but not rapamycin, causes modest acceleration of bladder and hindlimb recovery from spinal cord injury in rats

Abstract: Objectives: Erlotinib and Rapamycin are both in clinical use and experimental inhibition of their respective molecular targets, EGFR and mTORC1, has improved recovery from spinal cord injury. Our aim was to determine if daily Erlotinib or Rapamycin treatment started directly after spinal contusion injury in rats improves locomotion function or recovery of bladder function. Setting: Stockholm, Sweden Methods: Rats were subjected to contusion injuries and treated during the acute phase with either Erlotinib or R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…EGFR is a receptor tyrosine-protein kinase (TPK) in the plasma membranes, which plays a crucial regulatory role in cell survival, growth, differentiation, proliferation, apoptosis, and other signal pathways [36]. Recently, increasing evidence has suggested that EGFR has also been shown to participate in microvascular injury in diabetes, intestinal permeability, and BSCB permeability after SCI [12,13], indicating a role for EGFR in cellular barrier function [20]. Previous studies have demonstrated that EGFR activation was signi cant not only in astrocytes but also in microglia after SCI [17,19,28,37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EGFR is a receptor tyrosine-protein kinase (TPK) in the plasma membranes, which plays a crucial regulatory role in cell survival, growth, differentiation, proliferation, apoptosis, and other signal pathways [36]. Recently, increasing evidence has suggested that EGFR has also been shown to participate in microvascular injury in diabetes, intestinal permeability, and BSCB permeability after SCI [12,13], indicating a role for EGFR in cellular barrier function [20]. Previous studies have demonstrated that EGFR activation was signi cant not only in astrocytes but also in microglia after SCI [17,19,28,37].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that EGFR signal path is involved in functional regulation of cell barrier, including BSCB [8,14,20]. In order to assess whether blocking EGFR signal pathway could ameliorate disruption of BSCB after OGD/R injury, FITC-Dextran extravasation and TEER measurements were performed to assess permeability BSCB mode in vitro with OGD/R damage in this study.…”
Section: Egfr Blockade Ameliorate Ogd/r-induced Disruption Of Bscb Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the results do not support our hypothesis that selenium supplementation would result in improved outcomes following SCI. However, findings indicating bladder functional recovery without associated improvement in locomotor behavioral tasks suggest that these improvements in bladder function may be important markers for functional recovery[ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, long‐term functional improvement may not be feasible by mere mTOR inhibition. Rapamycin can adversely induce weight loss and affect peripheral vascular resistance or nociceptors, leading to a higher risk of cardiovascular dysfunction [124,125]. Nevertheless, as shown by Li et al (2014), lower doses of rapamycin combined with other therapeutic agents may decrease potential risks of toxicity and significantly boost its beneficial effects [111].…”
Section: Antibiotics With Therapeutic Effects In Scimentioning
confidence: 99%